Peranan Audit Internal dalam Meningkatkan Efektivitas Pengendalian Internal Inventory Suku Cadang di PT. Selamat Lestari Mandiri - Salsa Maulina; Sulaeman Sulaeman; Andri Indrawan (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to explain the role of internal audit in enhancing the effectiveness of spare parts inventory internal control at PT. Selamat Lestari Mandiri. The study employs a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation analysis. The research findings indicate that the implementation of internal audit for spare parts inventory has been well-executed, as evidenced by its adherence to the established schedule and procedures. The spare parts inventory internal control system is operating effectively, as demonstrated by its implementation, which largely complies with company procedures. Internal audit plays a crucial role in enhancing the effectiveness of spare parts inventory internal control at PT. Selamat Lestari Mandiri, as seen in its improvement and evaluation efforts regarding the implementation of spare parts inventory internal control, which have resulted in a reduction in spare parts discrepancies.